Comparative Study of Extra Capsular Cataract Extraction (ECCE) and Small Incision Cataract Surgery (SICS): Experience on Cataract Surgery in a Tertiary Center of Army Hospital, Kathmandu - Rajkarnikar, Sagar; Shrestha, Dhan Bahadur; Dhakal, Sachit; Shrestha, Ram; Thapa, Kamala; Gurung, Anu (Nepalese Journal of Ophthalmology, 2018)
Introduction: Cataract is a common ailment of the old age hindering daily activities leading to poor quality of life due to poor vision. It is the commonest cause of treatable blindness. In practice, extracapsular cataract excision and small incision cataract surgery are the two-common surgery for cataract these days in developing part like in Nepal. Between these two cataract surgeries, ECCE and SICS; SICS gives the better visual outcome. Methods: This retrospective cohort study was carried out including 286 eyes which were operated either by conventional extracapsular cataract extraction or small-incision cataract surgery. The patient’s demographics, preoperative vision, postoperative parameters/variables were studied from the patient’s record keeping. The postoperative visual outcome and complications were compared in both groups at the immediate post-operative period and at 8 weeks follow up period. Result: Among the total 286 cases, 138 underwent ECCE and 148 underwent SICS. 145 (50.6%) were right eye, 141 (49.3%) were left eye. Among total operated cases, 123 (43%) were mature cataract, 97 (33.9%) immature cataract, 66 (23.1%) hyper-mature cataract. In 172 cases (60.1%) there was a good vision, in 104 cases (36.4%) it was borderline while in rest 10 (3.5%) cases it was poor on the 60th postoperative day. There was the better visual outcome (≥6/18) with SICS (78.3%) than ECCE (40.5%) (p<0.001) on the 60th post-operative day. Among cases undergoing SICS the complications were less than ECCE. (p<0.001, OR=5.72 (2.10-15.51)). Conclusion: This study supports that SICS is safer than ECCE with less complication rate and better visual outcome in short term observation.